Expression and Function of Muscarinic Subtype Receptors in Bladder Interstitial Cells of Cajal in Rats - Wu, Yingbing; Shi, Chang; Deng, Jianping; Zhang, Xin; Song, Bo; Li, Longkun (Urology Journal, 2014)
Abstract Purpose: To locate the muscarinic (M) M2 and M3 receptors in bladder interstitial cells of Cajal (ICCs) and to determine the effects of M2 and M3 agonists on bladder ICCs. Materials and Methods: A total of 30 adult male Sprague-Dawley rats weighing 225-250 g were used in this study. Double-labeled fluorescence of muscarinic receptors and c-kit was performed for co-localization. To evaluate the effect of muscarinic agents on the excitation of bladder ICCs, we analyzed the inward current of bladder ICCs using the whole-cell patch clamp. The effect of muscarinic agents on the carbachol-induced inward currents was evaluated with the whole-cell patch clamp. Results: M2 and M3 receptors were confirmed in the stroma ICCs in rats’ bladders with double-labeled immunofluorescence. Spontaneous action potential was observed in freshly isolated bladder ICCs. The carbachol-induced inward Ca2+ current in ICCs can be blocked by atropine. The M2 receptor antagonist methoctramine (1 μM) showed a weak inhibitory capability on the inward Ca2+ current [from 74.8 ± 9.6 to 63.3 ± 13.8 Pascal (pA), n = 12, P = .03]. While the M3 receptor antagonist 4-diphenyl-acetoxy-N-methyl-piperidine methiodide (4-DAMP) (1 μM) significantly inhibited the inward Ca2+ current (from 78.4 ± 11.2 to 17.3 ± 7.9 pA, n = 12, P < .001). Conclusion: Bladder ICCs express M2 and M3 cholinergic receptors. Most muscarinic cholinergic receptor antagonists, especially the M3 antagonists, can effectively inhibit the carbamylcholine- induced inward current of bladder ICCs.